ONE-HELIX PROTEIN1 and 2 Form Heterodimers to Bind Chlorophyll in Photosystem II Biogenesis. Issue 1 (18th February 2020) - Hey, Daniel; Grimm, Bernhard
Abstract : Chlorophyll binding to the ONE-HELIX PROTEINS1/2 depends on heterodimer formation, mediated by conserved amino acids in their chlorophyll-binding motifs, and is essential for PSII biogenesis. Abstract: Members of the light-harvesting complex protein family participate in multiple processes connected with light sensing, light absorption, and pigment binding within the thylakoid membrane. Amino acid residues of the light-harvesting chlorophyll a / b -binding proteins involved in pigment binding have been precisely identified through x-ray crystallography experiments. In vitro pigment-binding studies have been performed with LIGHT-HARVESTING-LIKE3 proteins, and the pigment-binding ability of cyanobacterial high-light-inducible proteins has been studied in detail. However, analysis of pigment binding by plant high-light-inducible protein homologs, called ONE-HELIX PROTEINS (OHPs), is lacking. Here, we report on successful in vitro reconstitution of Arabidopsis ( Arabidopsis thaliana ) OHPs with chlorophylls and carotenoids and show that pigment binding depends on the formation of OHP1/OHP2 heterodimers. Pigment-binding capacity was completely lost in each of the OHPs when residues of the light-harvesting complex chlorophyll-binding motif required for chlorophyll binding were mutated. Moreover, the mutated OHP variants failed to rescue the respective knockout (T-DNA insertion) mutants, indicating that pigment-binding ability is essential for OHP function in vivo. The scaffold protein HIGH CHLOROPHYLL FLUORESCENCE244 (HCF244) is tethered to the thylakoid membrane by the OHP heterodimer. We show that HCF244 stability depends on OHP heterodimer formation and introduce the concept of a functional unit consisting of OHP1, OHP2, and HCF244, in which each protein requires the others. Because of their pigment-binding capacity, we suggest that OHPs function in the delivery of pigments to the D1 subunit of PSII.